An in situ self-charging triboelectric air filter with high removal efficiency, ultra-low pressure drop, superior filtration stability, and robust service life. (January 2023) - Wang, Yuxiao; Zhang, Xing; Jin, Xiangyu; Liu, Wanjun
Abstract: Applying air filters is a practical approach to protecting people from particulate matter (PM) pollution. However, high pressure drop or removal efficiency decay remains a considerable challenge for existing air filters while maintaining desirable removal efficiency. Generating charges by TENG technology is one of the significant advances for high-efficiency air filters. While TENG-based air filters usually require an additional TENG to achieve high removal efficiency that is only effective during TENG operation, resulting in increased redundancy and complexity of filters for practical applications. Using nonwoven carding and through-air bonding techniques, here we report an in situ S elf-charging T riboelectric A ir F ilter ( S-TAF ) consisting of silica nanoparticles modified polytetrafluoroethylene (PTFE) fibers and polypropylene/polyethylene (PP/PE) core-shell fibers. The S-TAF can be bipolarly charged in situ due to the triboelectrification effect between fibers during the carding process, thus dramatically enhancing the PM removal efficiency by electrostatic attraction. The unique core-shell structure of PP/PE fibers and the application of the through-air bonding process endowed the filter with a fluffy structure, high porosity, and large pore size, enabling the S-TAF with ultra-low pressure drop and robust service stability. Notably, the removal efficiency and quality factor (QF) of the S-TAF reached 99.28% and 0.19 Pa −1, and the pressure drop was only 26.46 Pa. Besides, the S-TAF also exhibited superior charge and filtration stability. Our unique design of the S-TAF may provide a new direction for fabricating high-performance air filters with integrated properties of high removal efficiency, ultra-low pressure drop, superior QF and filtration stability, and robust service life. Graphical Abstract: ga1 Highlights: The S-TAF consisting of silica nanoparticles modified PTFE fibers and PP/PE core-shell fibers is fabricated. The in situ triboelectrification effect between fibers during carding process results in the bipolarly charged S-TAF . The PP/PE fibers and through-air bonding process endow the S-TAF with ultra-low pressure drop and robust service stability. The PM removal efficiency, pressure drop, and QF of the S-TAF reach 99.28%, 26.46 Pa, and 0.19 Pa -1 .